Assessment of cardiac resynchronisation therapy in patients with wide QRS and non-specific intraventricular conduction delay: rationale and design of the multicentre randomised NICD-CRT study. Issue 11 (11th November 2016) - Eschalier, Romain; Ploux, Sylvain; Pereira, Bruno; Clémenty, Nicolas; Da Costa, Antoine; Defaye, Pascal; Garrigue, Stéphane; Gourraud, Jean-Baptiste; Gras, Daniel; Guy-Moyat, Benoît; Leclercq, Christophe; Mondoly, Pierre; et al.
Abstract : Introduction: Cardiac resynchronisation therapy (CRT) was initially developed to treat patients with left bundle branch block (LBBB). However, many patients with heart failure have a widened QRS but neither left-BBB nor right-BBB; this is called non-specific intraventricular conduction delay (NICD). It is unclear whether CRT is effective in this subgroup of patients. Methods and analysis: The NICD-CRT study is a prospective, double-blind, randomised (1:1), parallel-arm, multicentre trial comparing the effects of CRT in patients with heart failure, a reduced left ventricular ejection fraction (LVEF <35%) and NICD, who have been implanted with a device (CRT-pacemaker or CRT-defibrillator) that has or has not been activated. Enrolment began on 15 July 2015 and should finish within 3 years; 40 patients have already been randomised and 11 centres have agreed to participate. The primary end point is the comparison of the proportion of patients improved, unchanged or worsened over the subsequent 12 months. 100 patients per group are required to demonstrate a difference between groups with a statistical power of 90%, a type I error of 0.05% (two-sided) and a loss to follow-up of 10%. This trial will add substantially to the modest amount of existing data on CRT in patients with NICD and should reduce uncertainty for guidelines and clinical practice when added to the pool of current information. Ethics and dissemination: Local ethics committee authorisations have been obtained since May 2015. We will publish findings from this study in a peer-reviewed scientific journal and present results at national and international conferences. Trial registration number: NCT02454439; pre-results.